Isolated Abducens Nerve Palsy Following Pembrolizumab - Jaben, Korey A. (Neuroophthalmology, 2019)
Pembrolizumab is a checkpoint inhibitor targeting the programmed cell death 1 receptor of lymphocytes and is used in the treatment of solid tumours including melanoma. The authors report a 64-year-old man treated with pembrolizumab for stage IV cutaneous melanoma (primary cutaneous melanoma of the right lower back) with liver metastases. The patient developed a horizontal binocular diplopia due to an isolated unilateral cranial nerve VI palsy. Following 1 week of high dose oral steroid therapy and cessation of the drug, the patient’s nerve palsy and associated diplopic symptoms improved dramatically, and after 6 weeks of oral steroid taper and drug cessation, the palsy resolved completely. Few reports of checkpoint inhibitor autoimmune-induced isolated cranial nerve palsies have been described, and this is the first report of drug-induced isolated cranial nerve VI palsy.